An ineffective preparation? The scarce effect in primary school principals' practices of school leadership preparation and training in seven countries in Latin America. (March 2018) - Weinstein, José; Azar, Ariel; Flessa, Joseph
Latin American educational policy has relied on the assumption that better preparation can help school leaders improve their professional performance, thus improving quality of schools. Training programs for present or future school leaders have proliferated in the region, often publicly financed, but without enough evidence of their impact. Using data for seven Latin American countries from the Third Regional Comparative and Explanatory Study (TERCE), we seek to determine the association between school leaders' formal education and training received, with well recognized dimensions of school leadership practices reported by their teachers. We estimated linear regression models for each country in Latin America to determine the relationship between principals' preparation with indicators of educational leadership practices. Our results show that in most observed indicators of leadership practices the effect of education or training is marginal. We provide possible explanations for this finding, emphasizing the weaknesses in principals' initial selection processes and their deficiencies. We also consider schools' precarious conditions to support principals in order to put the knowledge they learned in training activities into practice. We point out the need to continue conducting specific studies on the effects of training on educational leadership among school leaders in the region, overcoming TERCE information restrictions.